2021
DOI: 10.1186/s12302-021-00463-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of silver-coated hollow poly(methylmethacrylate) microspheres for water decontamination

Abstract: Background Growing microbial resistance towards the existing antimicrobial materials appears as the greatest challenge for the scientific community and development of new antimicrobial materials has become an important research objective. Results In this work, antimicrobial activity of silver-coated hollow poly(methylmethacrylate) microspheres (PMB) having a diameter of 20–80 µm was evaluated against two bacterial strains, Gram-positive Bacillus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Also, there are many studies used biodegradable PCL-based films incorporated with PMMA and different drugs or nanoparticles which reported that these mats have no antimicrobial activities individually. 40–42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there are many studies used biodegradable PCL-based films incorporated with PMMA and different drugs or nanoparticles which reported that these mats have no antimicrobial activities individually. 40–42 …”
Section: Resultsmentioning
confidence: 99%
“…Also, there are many studies used biodegradable PCLbased films incorporated with PMMA and different drugs or nanoparticles which reported that these mats have no antimicrobial activities individually. [40][41][42] Different mats compositions of electrospun PMMA/PCL/ 6-MP nanofibers coded as (A) (8% PCL/4% PMMA/1% 6-MP), (B) (4% PCL/4% PMMA/1% 6-MP), and (C) (2% PCL/4% PMMA/1% 6-MP) were tested against extensively drug-resistant human pathogens (Klebsiella rhinoscleromatis, Streptococci sp., and Candida tropicalis) as shown in Figure 9. We noticed that, the highest inhibition zones were found for NFs (2% PCL/4% PMMA/1% 6-MP) (C) against Candida tropicalis (39.43±3.5), and Klebsiella rhinoscleromatis (35.37 ±0.9) followed by Streptococci sp., (29.25±2.2).…”
mentioning
confidence: 99%
“…Primarily, the cells getting in contact with silver take‐up the silver ions which damages the bacterial cell membrane. [ 44,45 ] Second, the generation of reactive oxygen species through inhibition of respiratory enzymes by silver ions damages the bacterial cell itself. In this study, when bacterial culture was treated with the inhibitory concentrations of photonic films, the E. coli physically contacts the photonic films, leading to cell wall pitting (Figure 6b), that is enough to cause bacterial death.…”
Section: Resultsmentioning
confidence: 99%
“…As the nanoparticles are embedded inside the polymer matrix, they are protected from external forces, which ultimately extends the lifetime of the functionalized textile. The antimicrobial properties of MNP-polymer composites have been extensively investigated [ 42 44 ] and research has gone into functionalizing textile fibers with the nanocomposites in situ [ 45 – 46 ]. Few studies seem to have been carried out on the coating of unaltered textile substrates with hybrid MNP-polymer films for antimicrobial applications.…”
Section: Introductionmentioning
confidence: 99%